2010
DOI: 10.1785/0120090030
|View full text |Cite
|
Sign up to set email alerts
|

Site- and Motion-Dependent Parametric Uncertainty of Site-Response Analyses in Earthquake Simulations

Abstract: We investigate the propagation of uncertainty in site-response analyses from the soil model parameters to the ground surface motion at three downhole array sites in the Los Angeles (LA) Basin. For this purpose, we develop realistic stochastic models of elastic and nonlinear dynamic soil properties using extensive site-specific and generic geotechnical data on the variability of soil properties. We also generate synthetic ground motions using a finite source dynamic rupture model over a wide range of magnitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…Many studies have demonstrated the limitations of the underlying assumptions of analytical soil models, even for relatively small-strain records (e.g., Baise et al, 2003;Boore, 2004;Kwok et al, 2008;Stewart and Kwok, 2008;Li and Assimaki, 2010;Rathje et al, 2010;Thompson et al, 2012). Site-response analyses are burdened with significant uncertainties in the input (rock) motion, soil parameters, constitutive model parameters, constitutive model assumptions, and other general assumptions (such as the 1D representation of the soil column that cannot account for horizontally propagating surface waves).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated the limitations of the underlying assumptions of analytical soil models, even for relatively small-strain records (e.g., Baise et al, 2003;Boore, 2004;Kwok et al, 2008;Stewart and Kwok, 2008;Li and Assimaki, 2010;Rathje et al, 2010;Thompson et al, 2012). Site-response analyses are burdened with significant uncertainties in the input (rock) motion, soil parameters, constitutive model parameters, constitutive model assumptions, and other general assumptions (such as the 1D representation of the soil column that cannot account for horizontally propagating surface waves).…”
Section: Introductionmentioning
confidence: 99%
“…Amplification effects due to the entire velocity-depth profile are likely to prove more useful to provide frequency-based amplification spectra. For future studies, it may be useful that processing of surface geophysical data used to measure V S profiles (e.g., ReMi, as used for this study, Louie, 2001;Scott et al, 2004Scott et al, , 2006Pancha et al, 2007) be revised to determine V S and its uncertainties as a function of depth (Li and Assimaki, 2010;Molnar et al, 2013) rather than averaged velocity values to selected depths (e.g. 30 m and 100 m as presented in this study).…”
Section: Discussionmentioning
confidence: 99%
“…Kwok et al [7] performed similar analyses on the Turkey Flat site by including three sets of MRD curves with full correlation between layers and found values ranging from 0.1 to 0.2 at short periods and very small values at long periods. Li and Assimaki [8] analyzed two sites in La Cienega using more than 50 MRD curve realizations and using a correlation coefficient of 0.15 between layers for nonlinear soil properties. For the first site, they computed standard deviation values of AFs due to varying MRD curves ranging from 0.3 and 0.4 at short periods and 0.2 at long periods.…”
Section: Background and Past Workmentioning
confidence: 99%